2018
DOI: 10.1038/s41388-018-0218-z
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase A-mediated phosphorylation regulates STAT3 activation and oncogenic EZH2 activity

Abstract: Polycomb Repressive Complex 2 (PRC2) member enhancer of zeste homologue 2 (EZH2) trimethylates histone H3 lysine 27 (H3K27me3), alters chromatin structure and contributes to epigenetic regulation of gene expression in normal and disease processes. Phosphorylation of EZH2 augmented EZH2 oncogenic activity in cancer but observations have been limited to serine 21 (S21) residue by protein kinase B. In addition, phosphorylation of the evolutionarily conserved T372 motif of EZH2 by p38 resulted in EZH2 interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…Corroborating our data, Koscso and colleagues demonstrated that adenosine, which binds to A2A and A2B receptors and stimulate the adenylyl cyclase to produce cAMP, has synergistic effect with IL-10 in inducing macrophage polarization towards an M2c profile in a STAT3-dependent manner [93]. Moreover, recent studies have argued that STAT3 activation can occur via PKA [94,95]. Although we have not investigated here whether db-cAMP-induced STAT3 activation was via PKA, we can hypothesize that PKA activation may be occurring in our settings of macrophage reprogramming.…”
Section: Discussionsupporting
confidence: 84%
“…Corroborating our data, Koscso and colleagues demonstrated that adenosine, which binds to A2A and A2B receptors and stimulate the adenylyl cyclase to produce cAMP, has synergistic effect with IL-10 in inducing macrophage polarization towards an M2c profile in a STAT3-dependent manner [93]. Moreover, recent studies have argued that STAT3 activation can occur via PKA [94,95]. Although we have not investigated here whether db-cAMP-induced STAT3 activation was via PKA, we can hypothesize that PKA activation may be occurring in our settings of macrophage reprogramming.…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly, upon Tyr372 phosphorylation of EZH2 by protein kinase A, pY372-EZH2 efficiently interacted with STAT3 protein. This non-canonical EZH2 interaction reduced cellular levels of STAT3 and altered STAT3 activation, leading to the downregulation of downstream target IL-6R in EOC [46]. Furthermore, tyrosine phosphorylation of EZH2 by JAK3 in lymphoid neoplasia was reported to promote dissociation of the polycomb repressive complex 2 (PRC2) complex leading to decreased global H3K27me3 levels while it switches EZH2 to a transcriptional activator [47], but studies in EOC are lacking.…”
Section: Other Gene Regulatory Mechanismsmentioning
confidence: 99%
“…A recent study reported that EZH2 phosphorylation at T372 reduced ovarian cancer cell proliferation, migration and tumor formation (Wan et al, 2018). The levels of EZH2-T372 phosphorylation in primary ovarian tumor samples were significantly lower than that in normal ovarian surface epithelium (Ozes et al, 2018). Wan et al reported that EZH2 phosphorylation at T311 by AMPK suppressed PRC2 activity and EZH2-pT311 correlated with better survival in ovarian and breast cancer patients (Wan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%